Testbed for Identity Management Proxies: A Practical Analysis of Shibboleth, SimpleSAMLphp, and SATOSA - Dalmazo, Luan Matheus Trindade; Farias, Jorge; Ribeiro Filho, Airton; Gomes, Luiza Kuze; Morais, Maria Amanda de Freitas; Sousa, Fiterlinge Martins de; Wangham, Michelle Silva (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
Identity Management is a field marked by ongoing discussions, among which the need for tools that enable integration between different communication protocols stands out. In this context, proxies have been widely used to facilitate interoperability between services. This paper presents a platform based on Keycloak designed for experimentation with the main proxies currently in focus: SATOSA, Shibboleth as a SAML proxy, and SimpleSAMLphp. The goal is to provide a testing and evaluation environment for these tools, while also proposing possible usage architectures based on the specific characteristics of each proxy. The results show that proxies can be applied in various scenarios, such as expanding service access to users from federations like CAFe.